Creation of a web portal for dissemination of accident information of underground coal mines of Eastern Coalfields Limited, India, using web GIS. (2016) - Basu, Tanima; Paul, P.K.
The web mapping application designed, displays the accident location and the cause of the accidents of the underground mines of Eastern Coalfields Limited (ECL). The application developed has attempted to create a platform for analysis of the accidents occurring in different underground mines of the study area and the dissemination of the same using web GIS. The web mapping application uses three-tier server side architecture to provide the framework for the portal. Dissemination of this information will lead to an increasing awareness among the mining engineers regarding the cause of occurrences of accidents, its severity and steps taken to curb this type of accidents, and thus will act as means of making the knowledge workers technically more effective to take necessary precautions to avoid such recurrences in future. This GIS portal is also aimed at a diversified audience including citizens who may be interested in information about the accidents.